Online Wedding During Pandemic the Perspective of Maqāṣid al-Syar'ah Imam al-Ghazāli - Alim, Syaiful (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Marriage is a primary and sacred need that is specifically regulated by religion. The sacred process in legalizing the relationship between men and women to prevent adultery and heinous acts. The multi-needs nature of marriage as a biological need and a social need must face problems with the Covid-19 virus that has hit all over the world and has stopped all social activities, including marriage. This article aims to examine how al-Ghazali with the construction of Maqāṣid al-Sharī’ah explores new laws in determining the permissibility of online marriage as a marriage solution during the Covid-19 pandemic. This research method uses a qualitative approach with the document study. The findings of this study: consideration of 4 (four) emergency arguments and “very ḍarar” dalil, and belongs to category categories of sensory ḍarar indrawi and ḍarar ‘ājilan. Assumptions offered by al-Ghazali include Al-Ḍarar Yazālu, Al-Ḍarar Yudfa’u Biqadri al-Imkāni considering the emergency conditions in which Al-Ḥājaṯ Tunzilu Manzilaṯ al-Ḍarūraṯ ‘Āmaṯ Kānata au Khāṣah and its Daf’a al-Qawāṭi’a. The conclusion of this study is that need for an online marriage that requires immediate action in the Covid-19 emergency because it is included in public and private problems around the world.